2017
DOI: 10.1111/tops.12285
|View full text |Cite
|
Sign up to set email alerts
|

Sketching the Invisible to Predict the Visible: From Drawing to Modeling in Chemistry

Abstract: Sketching as a scientific practice goes beyond the simple act of inscribing diagrams onto paper. Scientists produce a wide range of representations through sketching, as it is tightly coupled to model-based reasoning. Chemists in particular make extensive use of sketches to reason about chemical phenomena and to communicate their ideas. However, the chemical sciences have a unique problem in that chemists deal with the unseen world of the atomic-molecular level. Using sketches, chemists strive to develop causa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
86
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(94 citation statements)
references
References 41 publications
3
86
0
5
Order By: Relevance
“…In chemistry, several studies have shown that generating drawings of chemical processes at the sub-microscopic level can help students to interpret visualisations, make connections with prior knowledge, and promote understanding and modelbased reasoning (i.e., Ainsworth et al, 2011;Linn, 2011, 2013;Prain and Tytler, 2012;Akaygun and Jones, 2014;Cooper et al, 2017). Regarding physical models, Nicoll (2003) reported successful results using play-doh rather than traditional ball-and-stick kits to model molecules, and suggests that model-kits limit students in showing aspects like bond length or lone pairs.…”
Section: Student-generated Representationsmentioning
confidence: 99%
“…In chemistry, several studies have shown that generating drawings of chemical processes at the sub-microscopic level can help students to interpret visualisations, make connections with prior knowledge, and promote understanding and modelbased reasoning (i.e., Ainsworth et al, 2011;Linn, 2011, 2013;Prain and Tytler, 2012;Akaygun and Jones, 2014;Cooper et al, 2017). Regarding physical models, Nicoll (2003) reported successful results using play-doh rather than traditional ball-and-stick kits to model molecules, and suggests that model-kits limit students in showing aspects like bond length or lone pairs.…”
Section: Student-generated Representationsmentioning
confidence: 99%
“…For example, to explain the boiling point of water, students can be taught to draw the molecular structure of water and coordinate that with their understanding of energy transfer as sketched in a graph. In addition, drawing to support learning from simulations can be a constructive activity if students are asked to predict what they expect to see or to repeatedly revise the drawings they made as a consequence of interacting with a simulation (Cooper et al, 2017).…”
Section: The Purposes Of Drawingmentioning
confidence: 99%
“…In chemistry, several studies have shown that generating drawings of chemical processes at the sub-microscopic level can help students to interpret visualisations, make connections with prior knowledge, and promote understanding and model-based reasoning (Ainsworth et al, 2011;Akaygun & Jones, 2014;M. M. Cooper, Stieff, & DeSutter, 2017;Zhang & Linn, 2011).…”
Section: Student Generated Representations In Chemistrymentioning
confidence: 99%
“…M. Cooper, Stieff, & DeSutter, 2017;Zhang & Linn, 2011). It can be argued that chemistry learners are already required to generate representations of chemistry concepts, but according to (M. M. Cooper et al, 2017) this is more for copying and memorising canonical representations than for promoting students' model-based reasoning. They showed that if sketching is centrally integrated into classroom practice (rather than introduced as a separate, isolated activity), it can support model-based reasoning.…”
Section: Student Generated Representations In Chemistrymentioning
confidence: 99%